Unknown HIV status and the TB/HIV collaborative control program in Ethiopia: systematic review and meta-analysis - Balew Arega; Abraham Minda; Getachew Mengistu; Mulugeta Endale; Asnake Agunie (BMC, 2020)
Abstract Background Ethiopia has shown significant efforts to address the burden of TB/HIV comorbidity through the TB/HIV collaborative program. However, these diseases are still the highest cause of death in the country. Therefore, this systematic review and meta-analysis evaluated this program by investigating the overall proportion of unknown HIV status among TB patients using published studies in Ethiopia. Methods We conducted a systematic review and meta-analysis of published studies in Ethiopia. We identified the original studies using the databases MEDLINE/PubMed, and Google Scholar. The heterogeneity across studies was assessed using Cochran's Q test and I 2 statistics. The Begg's rank correlation and the Egger weighted regression tests were assessed for the publication bias. We estimated the pooled proportion of unknown HIV status among TB patients using the random-effects model. Results Overall, we included 47 studies with 347,896 TB patients eligible for HIV test. The pooled proportion of unknown HIV status among TB patients was 27%(95% CI; 21-34%) and with a substantial heterogeneity (I2 = 99.9%). In the subgroup analysis, the pooled proportion of unknown HIV status was 39% (95% CI; 25-54%) among children and 20% (95% CI; 11-30%) among adults. In the region based analysis, the highest pooled proportion of unknown HIV status was in Gambella, 38% (95% CI; 16-60%) followed by Addis Ababa, 34%(95% CI; 12-55%), Amhara,30%(95% CI; 21-40%),and Oromia, 23%(95% CI; 9-38%). Regarding the study facilities, the pooled proportion of unknown HIV status was 33% (95% CI; 23-43%) in the health centers and 26%(95% CI; 17-35%) in the hospitals. We could not identify the high heterogeneity observed in this review and readers should interpret the results of the pooled proportion analysis with caution. Conclusion In Ethiopia, about one-third of tuberculosis patients had unknown HIV status. This showed a gap to achieve the currently implemented 90-90-90 HIV/AIDS strategic plan in Ethiopia, by 2020. Therefore, Ethiopia should strengthen TB/HIV collaborative activities to mitigate the double burden of diseases.